Síndrome Serotoninérgico - Mora Azofeifa, Melissa (2019)
Serotonin syndrome is a potentially lethal adverse drug reaction that results from the therapeutic use of some drug, intentional overdose or involuntary drug interactions. Therefore, the syndrome is a predictable consequence of excess serotonergic agonism of central nervous system and of peripheral nervous system. This serotonin excess produces a spectrum of findings and clinical manifestations range from mild to severe symptoms that threaten the lives of patients. It is extremely important to recognize the syndrome for early diagnosis and the most appropriate approach, as it has significant impact on prognosis. In this document we review the most important aspects of the syndrome, its diagnosis and treatment.